Pengaruh Model Pembelajaran Flipped Classroom Terhadap Literasi Numerasi Siswa Kelas VIII SMP Swasta Gajah Mada - Shakila Salsabila; Mara Samin Lubis; Suci Dahlya Narpila (Universitas Palangka Raya, 2024)
Mathematics plays an important role in everyday life, including in the development of human thinking power, science, and technology, although it seems unreal and abstract. This study aims to determine the Effect of the Flipped Classroom Learning Model on Numeracy Literacy of Class VIII Students of Gajah Mada Private Middle School. The methodology of this study uses a quantitative quasi-experimental research type with a posttest in two classes. The population of this study were students of class VIII A, VIII B, VIII C at Gajah Mada Private Middle School with a total of 80 students. The sample in this study was class VIII B, and VIII C. The data sampling technique was carried out using the cluster random sampling technique. Data analysis was carried out with a posttest in both classes. Based on the results of the study, it can be concluded that